IMPOSITION POLICY, CHURCH AND URBANISTIC MODERNIZATION. THE CASE OF AVENIDA SEGUNDA , SAN JOSÉ, COSTA RICA (1951-1972) - Urbina Gaitán, Chester (2014)
In the extension was done at the south side of Avenida Segunda in San Jose from 1951to 1972 showed that the search for the regulation of traffic flow to pass along this citywas at the expense of its historical and architectural heritage and identity local. Becausethis extension at first did not have the technical and economic to support it, it is consideredthat it was hasty and improvised. This development project was supported by theMetropolitan Curia, who sold the land where the Sagrario was located to the capital’smunicipal council for demolition.